PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Nabiela, Seutya; -, Busra (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
Seeing the fact that there is no certainty regarding the share price that investors will get when investing in shares, investors need rational considerations by collecting various types of information needed to be able to make the right investment decisions. This research aims to determine the effect of financial performance on share prices of mining sector companies on the Indonesian Stock Exchange (BEI) for the 2019-2023 period. The method used in this research is quantitative methods with panel data analysis using eviews 12. The results of the research conclude that financial performance as measured by ROE, both simultaneously and partially, has an effect on share prices in mining sector companies on the Indonesian Stock Exchange (BEI) for the period 2019-2023.